Barriers to access to and success in higher education: intervention guidelines - Maree, Jacobus G (South African Journal of Higher Education, 2016)
Low throughput rates at schools and universities across South Africa are cause for great concern because of the resultant financial burden on the state, the increase in unemployment and inadequate delivery of much-needed highly skilled professionals. The advent of the fourth economic wave accompanied as it is by fundamental changes in the workplace globally calls for a judicious response from theorists, practitioners, researchers and learners. This article surveys the extent and possible causes of the low throughput rates in higher education and draws on the results of recent research projects to design intervention guidelines aimed at facilitating access to and success in higher education. A combined quantitative+qualitative approach is recommended.